(untitled) - Riley, R. C. (London, 1973)
This book introduce about useful for students enquiring into the distribution patterns of specific industries as much as those wishing to gain a broader ínight into the location of manufacturing as an entity.
Keywords: Nhà máy,Industrial location,Factories,Khu công nghiệp; Địa điểm,Location